Everything, everything - Yoon, Nicola; Yoon, David (New York Delacorte Press, 2015)
"The story of a teenage girl who's literally allergic to the outside world. When a new family moves in next door, she begins a complicated romance that challenges everything she's ever known. The narrative unfolds via vignettes, diary entries, texts, charts, lists, illustrations, and more"--
"Includes eight pages of photos from the movie!"--Jacket cover
1
Keywords: Friendship -- Fiction; Love -- Fiction; Racially mixed people -- Fiction; Severe combined immunodeficiency -- Fiction